REFLEXÕES SOBRE O ENSINO DA GEOMETRIA EM LIVROS DIDÁTICOS À LUZ DA TEORIA DE REPRESENTAÇÕES SEMIÓTICAS SEGUNDO RAYMOND DUVAL - Kluppel, Gabriela Teixeira (2012)
This dissertation presents an analysis of the geometry content of Mathematics textbooks. The research objectives were: to explain the specifics of Raymond Duval's semiotic representation theory, with respect to geometry, and to reveal to what extent these specifics are covered in the analyzed textbooks. The central research question we seek to answer is: to what extent does the organization of the geometry content of textbooks consider aspects of Raymond Duval's semiotic representation theory? As a theoretical basis, we use Raymond Duval’s works (2003, 2004). The research involved the analysis of textbooks published between 2002 and 2009, and the data collection and data analysis were supported by Bardin’s content analysis (2010). The research results indicate that the geometry discussed in textbooks has gaps in relation to aspects of Duval’s theory. These gaps relate to possibilities for the development of proposals for education. These are: the interaction between figural and discursive treatments; the linkage between figural register and discourse to minimize the phenomenon of non-congruent semantics (made possible by setting guidelines for submission, problem solving and the demonstration of theorems); mereological or visual modifications responsible for the operative capture of figures, and finally, the resolution of exercises which require organization to enable a systematic variation of visibility factors to facilitate the non-use of definitions or theorems.